Potential of fresh POME as a growth medium in mass production of Arthrospira platensis - Sukumaran, Puganeswary; Nulit, Rosimah; Zulkifly, Shahrizim; Halimoon, Normala; Omar, Hishamuddin; Ismail, Ahmad (Excellent Publishers, 2014)
The prospects of utilizing fresh Palm Oil Mill Effluent (POME) as an alternative and inexpensive growth medium in Arthrospira platensis cultivation was evaluated in outdoor large scale cultivation system. The aim of this study is to find the optimum fresh POME concentration (T1; 0%, T2; 1%, T3; 2%, T4; 3% and T5; 4%v/v) for good growth and pigments production of A. platensis as in control (modified Kosaric medium). The relative performance of the different concerntrations of fresh POME were investigated with respect to their productivity, specific growth rate and pigments production A. platensis culture in T2 (1% v/v fresh POME)had significantly higher (p<0.05) productivity (0.211 ±0.0034g L-1 d-1)and specific growth rate( 0.250±0.0026 μ d-1)compare to control and other treatments.